The Ideator’s Bias: How Identity-Induced Self-Efficacy Drives Overestimation in Employee-Driven Process Innovation - Fuchs, Christoph; Sting, Fabian J.; Schlickel, Maik; Alexy, Oliver (Academy of Management Journal, 2019)
Grasping the true value of ideas is essential for corporate innovation success. When it comes to forecasting the value of one’s own innovation ideas, however, people may err systematically. In this paper, we shed light on this ideator’s bias, and examine when and why certain ideas are more prone to biased evaluations. Specifically, we argue that biased idea evaluations depend on the self-efficacy that ideators may derive from their specific role and social identity in the firm when generating a specific idea. We test our theoretical predictions of such a situation-specific perspective on overconfidence by using a corporate dataset on process innovations and their valuations. Furthermore, we triangulate our predicted mechanism and rule out alternative explanations through a series of additional interviews and four scenario-based experiments. Consistent with our situation-specific, identity-based account, we find that ideas from employees at a higher (vs. lower) organizational level, and from employees generating ideas in groups (vs. individually) are more prone to an ideator’s bias. In doing so, our study helps explain when the ideator’s bias prevails in a real-life organizational context, raises caution about some current proxies to identify high-potential ideas, and provides fresh insights to established theories around overconfidence and self-efficacy.